(untitled) (Biodiversitas Journal of Biological Diversity, 2006)
Burahol (Stelechocarpus burahol (Blume) Hook & Thomson) is one of fruit tree that originally was founded in Indonesia. Traditionally burahol is used as natural deodorance, but due to low economic value, the cultivation program of this plant species is almost abandoned. Regarding to this situation, currently this plant species could be categorized as one of endangered species. At present, economic value of this fruit is almost neglected and this is the main reason why not many people interested to cultivate this plant. In order to change the people opinion on this plant and to improve it economic value, study on the chemical content of this plant had been carried out. From the research work, it was founded that burahol fruit have a significant content of anti-oxidative compound. From the anti-oxidative analysis using DPPH (1,1-diphinil pycril hidrazil) method, the lowest IC50 was showed by n-buthanol extract of flower (22.44 ppm) and ethyl acetate extract of fruit (29.12 ppm). Flower part also showed low IC50 of ethyl acetate extract (35.07 ppm). Further purification through fractionation process of the plant extract was surprisingly followed by the decrease of anti-oxidative activity. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: anti-oxidative, 1,1-diphinil pycril hidrazil , burahol.